Three-Wheel Table Tennis Ball Throwing Machine - Teo, Shun Yang (Universiti Sains Malaysia, 2018)
A three-wheel table tennis ball throwing machine is designed and fabricated. The study on speed combination of three-wheel is performed to produce several spin with different kind of three wheel speed combinations. A control system is needed to produce the ball spin based on the input delivered. This project is aimed to design an affordable, programmable and well perform three-wheel table tennis ball throwing machine. The machine has 13 inputs and 13 outputs. The outputs are different type of ball spins. The power supply providing power to the machine will current from 240V AC to 12V DC. The Arduino Mega 2560 microcontroller is used as the controller to control the motors. A high torque DC motor is used to rotate the round wooden disc where it can control the ball feed rate. A low torque high speed DC brushed motor is used to spin the fan so it can blow the ball to reach the shooting place. Three high speed high torque DC brushed motors are used to shoot the table tennis ball from machine. They receive different PWM signals and provide different results to rotate the table tennis ball. A potentiometer is used to control the speed of motor hence varies the reading of PWM in multiplication method. The machine can give Top Spin, Back Spin, Side Spin, No Spin and Back Side Spin with the choice of heavy or light spin. The different speed ratio of the motors are giving different ball spins and number of spins of ball per minute. To achieve heavy top spin, the ratio of motor speed is Wheel A: B: C= 6.8: 1: 1 while the light top spin is Wheel A: B: C= 1.8: 1: 1. The heavy clockwise side spin require speed ratio of Wheel A: B: C= 3.5: 3.2: 0 while the light clockwise side spin require speed ratio of Wheel A: B: C= 2.5: 1: 1. The speed ratio of motors are remain same to produce the ball spin. The motor speed can be varied by adjusting the speed level.